Patient and provider factors associated with enrolment in the pre-end-stage renal disease pay-for-performance programme in Taiwan: a cross-sectional study. Issue 9 (13th September 2019) - Hu, Hsiao-Yun; Jian, Feng-Xuan; Lai, Yun-ju; Yen, Yung-Feng; Huang, Nicole; Hwang, Shang Jyh
Abstract : Objective: The incidence and prevalence of end-stage renal disease (ESRD) in Taiwan have been ranked the highest worldwide. Therefore, the National Health Insurance Administration has implemented the pre-ESRD pay-for-performance (P4P) programme since November 2006, which had significantly reduced the incidence of dialysis and all-cause mortality. This study aimed to identify the factors associated with the enrolment in the pre-ESRD P4P programme. Design: Cross-sectional study. Setting: The National Health Insurance research database 2007–2012 in Taiwan. Participants: Patients with prevalent pre-ESRD aged more than 18 years between January 2007 and December 2012 were enrolled. Patient demographics and hospital characteristics between P4P and non-P4P groups were compared. A logistic regression model was used to analyse the factors associated with P4P enrolment, and a generalised estimating equation was used to verify the results. Primary outcome measure: Enrolment in the pre-ESRD P4P programme. Results: In total, 82 991 patients were enrolled in the programme, with a 45.6% participation rate. Patients who were males (adjusted OR (AOR)=0.89, 95% CI=0.86 to 0.91) and employed (AOR=0.95, 95% CI=0.92 to 0.97) had a significantly lower probability to be enrolled in the programme. Older patients (66–75 years old, AOR=1.23, 95% CI=1.14 to 1.33) and those with higher Charlson Comorbidities Index (CCI 5+, AOR=4.01, 95% CI=3.55 to 4.53) tended to be enrolled in the programme, while those in the 76+ years age group were not (AOR=1.03, 95% CI=0.95 to 1.13). Hospitals located in the central (AOR=1.48, 95% CI=1.05 to 2.08) and Kao-Ping regions (AOR=1.62, 95% CI=1.18 to 2.22) also tended to enrol patients in the pre-ESRD P4P programme. Enrolment rates increased over time. Conclusion: Pre-ESRD patients of the female gender, greater age and more comorbidities were more likely to be enrolled in the pre-ESRD P4P programme. Healthcare providers and health authorities should focus attention on patients who are male, younger and with less comorbidities to improve the healthcare quality and equality for all pre-ESRD patients.